IDNLearn.com makes it easy to find accurate answers to your specific questions. Get the information you need from our community of experts who provide accurate and comprehensive answers to all your questions.
Sagot :
Alright, let's analyze each of the given systems of linear equations step-by-step and determine the number of solutions for each system.
### System 1:
[tex]\[ y = -2x + 5 \][/tex]
[tex]\[ 2x + y = -7 \][/tex]
Step-by-Step:
1. Substitute [tex]\( y = -2x + 5 \)[/tex] into [tex]\( 2x + y = -7 \)[/tex]:
[tex]\[ 2x + (-2x + 5) = -7 \][/tex]
2. Simplify the equation:
[tex]\[ 5 = -7 \][/tex]
This results in a contradiction. Therefore, the first system has no solution.
### System 2:
[tex]\[ y = x + 6 \][/tex]
[tex]\[ 3x - 3y = -18 \][/tex]
Step-by-Step:
1. Substitute [tex]\( y = x + 6 \)[/tex] into [tex]\( 3x - 3y = -18 \)[/tex]:
[tex]\[ 3x - 3(x + 6) = -18 \][/tex]
2. Simplify the equation:
[tex]\[ 3x - 3x - 18 = -18 \implies -18 = -18 \][/tex]
This is an identity, which means the equations are dependent, and every solution of the first equation is also a solution of the second equation. Thus, the second system has infinitely many solutions.
### System 3:
[tex]\[ y = -4x + 11 \][/tex]
[tex]\[ -6x + y = 11 \][/tex]
Step-by-Step:
1. Substitute [tex]\( y = -4x + 11 \)[/tex] into [tex]\( -6x + y = 11 \)[/tex]:
[tex]\[ -6x + (-4x + 11) = 11 \][/tex]
2. Simplify the equation:
[tex]\[ -6x - 4x + 11 = 11 \implies -10x + 11 = 11 \][/tex]
3. Solve for [tex]\( x \)[/tex]:
[tex]\[ -10x = 0 \implies x = 0 \][/tex]
4. Substitute [tex]\( x = 0 \)[/tex] back into [tex]\( y = -4x + 11 \)[/tex]:
[tex]\[ y = -4(0) + 11 = 11 \][/tex]
So, the solution is [tex]\( (0, 11) \)[/tex]. Therefore, the third system has one solution.
### Summary
- The system [tex]\( y = -2x + 5 \)[/tex] and [tex]\( 2x + y = -7 \)[/tex] has no solution.
- The system [tex]\( y = x + 6 \)[/tex] and [tex]\( 3x - 3y = -18 \)[/tex] has infinitely many solutions.
- The system [tex]\( y = -4x + 11 \)[/tex] and [tex]\( -6x + y = 11 \)[/tex] has one solution.
Thus, the systems match with the number of solutions as follows:
- [tex]\( y = -2x + 5 \)[/tex] and [tex]\( 2x + y = -7 \)[/tex] → no solution
- [tex]\( y = x + 6 \)[/tex] and [tex]\( 3x - 3y = -18 \)[/tex] → infinitely many solutions
- [tex]\( y = -4x + 11 \)[/tex] and [tex]\( -6x + y = 11 \)[/tex] → one solution
### System 1:
[tex]\[ y = -2x + 5 \][/tex]
[tex]\[ 2x + y = -7 \][/tex]
Step-by-Step:
1. Substitute [tex]\( y = -2x + 5 \)[/tex] into [tex]\( 2x + y = -7 \)[/tex]:
[tex]\[ 2x + (-2x + 5) = -7 \][/tex]
2. Simplify the equation:
[tex]\[ 5 = -7 \][/tex]
This results in a contradiction. Therefore, the first system has no solution.
### System 2:
[tex]\[ y = x + 6 \][/tex]
[tex]\[ 3x - 3y = -18 \][/tex]
Step-by-Step:
1. Substitute [tex]\( y = x + 6 \)[/tex] into [tex]\( 3x - 3y = -18 \)[/tex]:
[tex]\[ 3x - 3(x + 6) = -18 \][/tex]
2. Simplify the equation:
[tex]\[ 3x - 3x - 18 = -18 \implies -18 = -18 \][/tex]
This is an identity, which means the equations are dependent, and every solution of the first equation is also a solution of the second equation. Thus, the second system has infinitely many solutions.
### System 3:
[tex]\[ y = -4x + 11 \][/tex]
[tex]\[ -6x + y = 11 \][/tex]
Step-by-Step:
1. Substitute [tex]\( y = -4x + 11 \)[/tex] into [tex]\( -6x + y = 11 \)[/tex]:
[tex]\[ -6x + (-4x + 11) = 11 \][/tex]
2. Simplify the equation:
[tex]\[ -6x - 4x + 11 = 11 \implies -10x + 11 = 11 \][/tex]
3. Solve for [tex]\( x \)[/tex]:
[tex]\[ -10x = 0 \implies x = 0 \][/tex]
4. Substitute [tex]\( x = 0 \)[/tex] back into [tex]\( y = -4x + 11 \)[/tex]:
[tex]\[ y = -4(0) + 11 = 11 \][/tex]
So, the solution is [tex]\( (0, 11) \)[/tex]. Therefore, the third system has one solution.
### Summary
- The system [tex]\( y = -2x + 5 \)[/tex] and [tex]\( 2x + y = -7 \)[/tex] has no solution.
- The system [tex]\( y = x + 6 \)[/tex] and [tex]\( 3x - 3y = -18 \)[/tex] has infinitely many solutions.
- The system [tex]\( y = -4x + 11 \)[/tex] and [tex]\( -6x + y = 11 \)[/tex] has one solution.
Thus, the systems match with the number of solutions as follows:
- [tex]\( y = -2x + 5 \)[/tex] and [tex]\( 2x + y = -7 \)[/tex] → no solution
- [tex]\( y = x + 6 \)[/tex] and [tex]\( 3x - 3y = -18 \)[/tex] → infinitely many solutions
- [tex]\( y = -4x + 11 \)[/tex] and [tex]\( -6x + y = 11 \)[/tex] → one solution
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is your go-to source for dependable answers. Thank you for visiting, and we hope to assist you again.